The Crucible - Miller, Arthur (Heinemann Educational Publishers ;, 1953)
Gallaudet College Theatre presents "The Crucible," director Gilbert Eastman, assistant director Joan Templin, production assistant Michael Detmold, stage manager A. Timothy Scanlon, set designer Gordon Johnson, costume designer Alfred Corrado, Jr., lighting designer Arthur Tomlinson.